Vaccines against Ebola virus and Marburg virus: recent advances and promising candidates - John J. Suschak; Connie S. Schmaljohn (Taylor & Francis Group, 2019)
The filoviruses Ebola virus and Marburg virus are among the most dangerous pathogens in the world. Both viruses cause viral hemorrhagic fever, with case fatality rates of up to 90%. Historically, filovirus outbreaks had been relatively small, with only a few hundred cases reported. However, the recent West African Ebola virus outbreak underscored the threat that filoviruses pose. The three year-long outbreak resulted in 28,646 Ebola virus infections and 11,323 deaths. The lack of Food and Drug Administration (FDA) licensed vaccines and antiviral drugs hindered early efforts to contain the outbreak. In response, the global scientific community has spurred the advanced development of many filovirus vaccine candidates. Novel vaccine platforms, such as viral vectors and DNA vaccines, have emerged, leading to the investigation of candidate vaccines that have demonstrated protective efficacy in small animal and nonhuman primate studies. Here, we will discuss several of these vaccine platforms with a particular focus on approaches that have advanced into clinical development.